Kriopreservasi Sperma Manusia: Systematic Review - Diana Fadhilah; Adam Raihan Priambada; Zozy Aneloi Noli; Rita Maliza (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This study aims to identify the types of methods and effects of human sperm cryopreservation. This review was written using a literature review method from international databases such as Scopus and PubMed. The results of the research show that by choosing a cryopreservation method, choosing a cryoprotectant agent such as TAT-PRDX2, canthaxanthin, or Holotheria parva coleomic extract, can increase sperm motility, viability and integrity after cryopreservation, the right cryoprotectant agent can defend cells from oxidative stress and fragmentation DNA. Keywords: Cryopreservation, Human, Sperm